Electrodeposition‐based 3D Printing of Metallic Microarchitectures with Controlled Internal Structures. Issue 32 (27th April 2015) - Seol, Seung Kwon; Kim, Daeho; Lee, Sanghyeon; Kim, Jung Hyun; Chang, Won Suk; Kim, Ji Tae
<x xml:space="preserve">Abstract</x> 3D printing of metallic microarchitectures with controlled internal structures is realized at room temperature in ambient air conditions by the manipulation of metal ion concentration and pulsed electric potentials in the electrolyte meniscus during the meniscus‐guided electrodeposition. Precise control of the printing nozzle enables the drawing of complex 3D microarchitectures with well‐defined geometries and positions.